Radiological early detection of lung cancer in patients with chronic pulmonary diseases - Hend M. Sayed; Summar EL-Morshidy; Mostafa A. Sayed; Heba M. Mohammed; Samiaa Hamdy Sadek (The Egyptian Journal of Bronchology)
Abstract Background Lung cancer (LC) is an important cause of cancer deaths all over the world. The history of chronic chest diseases is considered a risk factor for LC development, so searching for LC in chronic chest disease patients is fundamental. Objectives Low-dose computed tomography’s role in early detection of LC in those patients. Methods This study is an observational cross-sectional study design. It included 303 newly admitted patients with chronic chest diseases to the Chest Department, Assiut University Hospital, Egypt from March 2023 to April 2024. All patients are subjected to a complete history and examination. Chest X-ray, arterial blood gases, and spirometry for confirming diagnosis and assessment of disease severity. Low-dose CT chest (LDCT) was done for all patients. Results The current study revealed that patients with lung LC had significantly higher age, male gender predominance, smoking, and higher frequency of exacerbation during the last year. Also, about 94.1% of lung cancer patients had COPD, there was statistically significant kappa agreement between CT and histopathology in the diagnosis of malignancy (Kappa = 0.914, P-value < 0.001), low dose computed tomography has a sensitivity of 100.0%, specificity of 99.0%, the positive predicted value of 85.0% and negative predicted value of 100.0% and accuracy of 99.0% in the detection of lung cancer. LDCT chest showed higher sensitivity compared to chest X-ray (100%, and 35% respectively) in predicting lung cancer in patients with chronic lung disease. Conclusions The predictors significant for developing LC in chronic pulmonary disease patients are old age, smoking, and frequent exacerbation in the last year, also LDCT chest is recommended for LC prediction in patients with chronic lung diseases. Trial registration Clinical trial.gov: NCT06074978.